2003
DOI: 10.1081/mst-120022776
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated Thermal Microscopy of the Tool–Chip Interface in Machining

Abstract: This paper presents the results of calibrated, microscopic measurement of the temperature fields at the tool -chip interface during the steady-state, orthogonal machining of AISI 1045 steel. The measurement system consists of an infrared imaging microscope with a 0.5 mm square target area, and a spatial resolution of less than 5 mm. The system is based on an InSb 128 Â 128 focal plane array with an allreflective microscope objective. The microscope is calibrated using a standard blackbody source from NIST. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 16 publications
2
54
0
Order By: Relevance
“…However, when FEM simulations were performed to model a series of orthogonal cutting experiments on AISI 1045 of Davies, et al [6], in which careful measurements were made of the temperature along the tool-chip interface, it was found that Tlusty's method with no thermal softening, i.e., = ∞, provided better peak temperature predictions than did the FEM code using Jaspers' Johnson-Cook model [9]. Based on this information, it is likely that Equation (2) with = ∞ will give the best peak temperature prediction in AISI 1075.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, when FEM simulations were performed to model a series of orthogonal cutting experiments on AISI 1045 of Davies, et al [6], in which careful measurements were made of the temperature along the tool-chip interface, it was found that Tlusty's method with no thermal softening, i.e., = ∞, provided better peak temperature predictions than did the FEM code using Jaspers' Johnson-Cook model [9]. Based on this information, it is likely that Equation (2) with = ∞ will give the best peak temperature prediction in AISI 1075.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than use a finite-element code for this purpose, a simplified method first introduced by Boothroyd [8] is used. It turns out that this method, as modified by Tlusty [1], can give a better peak temperature estimate than some finite element simulations [6,9].…”
Section: One-dimensional Cutting Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The detrimental effects of temperature elevation in material removal highlight the importance of detailed studies of thermal interaction in the active material volume. Traditionally, studies of such a topic have been confined to analytical [3][4][5], numerical [6][7][8], and experimental [9][10][11][12][13][14][15][16] determination of the temperature rise during machining. Critical consideration of the literature, however, reveals that despite it's crucial influence on the mechanics of material removal, physics of thermal energy transport within the critical areas of contact (toolworkpiece and tool-chip) is by far still unexplored.…”
Section: Introductionmentioning
confidence: 99%